2014
DOI: 10.1002/jcp.24714
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin Peptides as Potential Regulators of Hepatic Fibrosis Through Apoptosis of Hepatic Stellate Cells

Abstract: The turnover of extracellular matrix (ECM) components can generate signals that regulate several cellular functions such as proliferation, differentiation, and apoptosis. During liver injury, matrix metalloproteases (MMPs) production is enhanced and increased levels of peptides derived from extracellular matrix proteins can be generated. Synthetic peptides with sequences present in extracellular matrix proteins were previously found to induce both stimulating and apoptotic effects on several cell types includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 58 publications
1
25
0
Order By: Relevance
“…86,87 In agreement with the mentioned role of TIMP-1 in HSC apoptosis, 71 MMP-2 can promote HSC apoptosis through cleavage of N-cadherin, 86 typical marker of activated myofibroblasts. Recently, the role of degradation products produced by MMPs in regulation of fibrosis has been proposed; cleaved fibronectin peptides induced apoptosis in HSC line and stimulated MMP-9 secretion from human monocytes.…”
Section: Mmps In Recovery Of Liver Fibrosissupporting
confidence: 66%
See 1 more Smart Citation
“…86,87 In agreement with the mentioned role of TIMP-1 in HSC apoptosis, 71 MMP-2 can promote HSC apoptosis through cleavage of N-cadherin, 86 typical marker of activated myofibroblasts. Recently, the role of degradation products produced by MMPs in regulation of fibrosis has been proposed; cleaved fibronectin peptides induced apoptosis in HSC line and stimulated MMP-9 secretion from human monocytes.…”
Section: Mmps In Recovery Of Liver Fibrosissupporting
confidence: 66%
“…Recently, the role of degradation products produced by MMPs in regulation of fibrosis has been proposed; cleaved fibronectin peptides induced apoptosis in HSC line and stimulated MMP-9 secretion from human monocytes. 87 Zbodakova et al Inflammation and regulation of TNFa signaling in liver injury ADAM17 was originally discovered as a protease effectively cleaving TNFa and is therefore also known as TNFaconverting enzymes. TNFa is pivotal in many pathological conditions of the liver and has a distinct effect on hepatocytes depending on the strength and duration of a signal.…”
Section: Mmps In Recovery Of Liver Fibrosismentioning
confidence: 99%
“…Cells were grown in MEM supplemented with 10% heat-inactivated FBS plus 1% penicillin and streptomycin and 1% non-essential amino acids. LX-2, (Lieming Xu-2) is a human non-tumoral immortalized cell line that was generously provided by Dr. Scott Friedman [29]. This cell line was generated by the immortalization of HSC with SV 40 large T antigen, followed by low serum conditions.…”
Section: Materials and Chemicalsmentioning
confidence: 99%
“…It has been shown that the levels of IL-1 resulting from autocrine action in fibroblasts and paracrine action in Kupffer cells are positively associated with the severity of liver fibrosis. IL-1 also plays an important role in the synthesis and deposition of ECM materials through the upregulation of tissue inhibitor of metalloproteinases (TIMP) and the downregulation of matrix metalloproteinases (MMPs) (Mòdol et al, 2015). Kupffer cells also have multiple biological effects on hepatocytes, HSCs, and endothelial cells.…”
Section: Expression Of Tlrs In Liver Fibrosismentioning
confidence: 99%